Along‐Track Marine Geoid Resolution Enhancement With SWOT - Xu Chen; Shengjun Zhang; Ole Baltazar Andersen; Yongjun Jia (Earth and Space Science)
Abstract Satellite altimetry has been the major data source for marine geoid determination·and gravity recovery in recent decades. In general, altimetry‐derived geoid and gravity anomaly models are typically released with a 1' × 1' gridding interval. However, their actual spatial resolution is far lower than the nominal ∼2 km level. Therefore, analyzing the marine geoid resolution capability from satellite altimetry observations is crucial for marine gravity recovery studies. The Surface Water and Ocean Topography (SWOT) Mission is a newly launched satellite using advanced radar technology to make headway in observing the·variability of water surface elevations, providing new information through along‐track and across‐track two‐dimensional swath observations. Here, we present the analysis results of marine geoid resolution capability for both typical conventional nadir altimeters and the SWOT Ka‐band radar interferometer (KaRIn) in 2° × 2° bins worldwide between 60°N and 60°S. We demonstrate the potential of SWOT KaRIn to capture along‐track short‐wavelength signals below 10 km and analyze the bin‐based statistics of key marine geophysical factors correlated with this marine geoid resolution capability. Generally, SWOT KaRIn exhibits better marine geoid resolution capability over bins with large‐scale seamounts or trenches.